Cyberpragmatics Lintas Budaya: Perbandingan Strategi Kesantunan dalam Komunikasi Digital Indonesia dan Barat pada Media Sosial - Nur Lailiyah; Teguh Setiawan; Madiawati Mamat@ Mustaffa (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study aims to examine the comparison of politeness strategies in digital communication between Indonesian and Western societies through a cross-cultural cyberpragmatic approach. The study focuses on how users from both cultures practice linguistic politeness in digital platforms such as social media and instant messaging applications. The method used is a qualitative study employing pragmatic discourse analysis techniques. Data consists of 90 utterances from conversations on Instagram (30 utterances), WhatsApp (30 utterances), and Twitter (30 utterances) from both cultural groups. The findings indicate that Indonesian society tends to use negative politeness strategies more explicitly, such as honorifics, apologies, and euphemisms, while Western society more frequently employs positive politeness emphasizing familiarity, recognition of individual identity, and the use of humor. These differences reflect underlying cultural values such as collectivism versus individualism. This study contributes to 1) understanding the dynamics of cross-cultural digital communication and its implications for the development of global communication ethics in the digital age, and 2) providing a crucial foundation for developing more effective cross-cultural digital communication guidelines, whether in business, diplomacy, or education contexts.